Economic and Social Conditions and their Impact on the Reality of Basic Education and its Development in Egypt 1982-1992 (Journal of the College of Education for Women, 2024)
The study included the most important issues that Egyptian society was suffering from during the period (1982-1992), i.e. the problem of (education), which is considered the most expensive human investment made by the nation in order to protect its future. Education is the real gateway to the new world with all its hopes, aspirations and challenges because it contributes to achieving social stability and enhancing the comprehensive development process. This comes due to the nature of the era in which we live, which is an increasing explosion of knowledge and a massive revolution in communications, information and technology, and the conflicts imposed by various entities over superiority and distinction, and the availability of an educated person capable of controlling changes for his benefit and for the benefit of his society. One of the most important means that can play a major role in this field is the media, which is supposed to have a main role in urging the government to develop strategic policies to develop basic education as they help education to achieve its goals towards literature, science, art and culture, and its responsibility towards its readers in providing them with information with which they can keep the civilization and human progress in every place and field. Among these educational issues is the issue of (basic education), which represents the main focus of this study, as all parties in society had to provide visions of the reality of education in general and basic education in particular.